Sol-gel synthesis, optical properties, morphology and photocatalytic activity of titania films modified with ethanolamines as nitrogen source - Linnik, O.P.; Shestopal, N.O.; Smirnova, N.P.; Eremenko, A.М.; Stanculescu, A.; Socol, M. (Поверхность, 2012)
In this work the titania films modified with ethanolamines are synthesized by sol-gel method using two different routes. Introduction of template during sol ripening leading to the formation of porous structure and a single stage synthesis resulting in non-porous surface are proposed. The optical properties and calculated band-gap values of the films are presented. The titania particle size of the modified films is increased in comparison with the bare one as results of Root mean square (RMS) and Roughness average (Ra) values. The influence of the synthesis conditions and structure of ethanolamines on the photocatalytic activity under visible light are reported.